Pelatihan Pengolahan Tulang Ikan Nila menjadi Abon di Desa Sebangun Kecamatan Sebawi - Maryono Maryono; Dewi Merdekawati; Gusti Randy Pratama; Risqy Pricillia Nanda; Nirawati (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
The utilization of fish waste needs to be widely applied to the community, especially at the household scale. One of them is by carrying out community service activities, the purpose of this activity is to socialize as well as provide training on processing tilapia bones into shreds to housewives in Sebangun village. The method of service activities starts from planning, observation or initial visits, preparation, and implementation of activities. The training steps begin with the delivery of theory then demonstration or training as well as direct assistance to participants. The results of the activity achieved were that the participants had known the process of making shredded tilapia bones and the standard process of product packaging. In addition, it is hoped that the results of this activity can be disseminated, fulfill children's nutrition, and can improve the community's economy.